Long-term outcome of knee and ankle injuries in elite football - Larsen, E.; Jensen, P. K.; Jensen, P. R. (Scandinavian Journal of Medicine & Science in Sports, 1999)
To estimate the risk and evaluate the long-term outcome of knee and ankle injuries in former national team elite football, 69 players were randomly selected, followed by clinical and stress radiographic examinations. Thirty-nine players (49 knees) had had knee injuries and 29 ankle injuries (35 ankles). The median time from injury until study examination was 25 years. The knee injuries were tears of the medial collateral ligament (MCL) in 24 cases combined with rupture of the anterior cruciate ligament (ACL) and meniscus lesions in three. Meniscus lesions had occured in 17 cases including three combined with ACL and MCL and another two with ACL ruptures. Isolated rupture of the ACL had occured in four cases. The ankle lesions were in 26 of 35 cases ruptures of the lateral ligaments. In all, 12 players hat completely stopped football and three had changed occupation. Signs of arthritis were present in 63% of the injured knees and in 33% of the injured ankles. The incidence of arthritis in the group of 17 uninjured players was 26% in the knee and 18% in the ankle. In elite football players knee and ankle injuries seem to have a serious long-term outcome, but also uninjured players have a higher risk of developing arthritis than the normal population. Untersucht wurden die längerfrsitigen Zustände nach Knie- und Fußgelenkverletzungen ehemaliger Fußballnationalspieler. dazu wurden 69 Spieler im Alter von 52 bis 71 Jahren klinisch und radiographisch untersucht. Bei 39 Spieelrn (49 Knie) lagen Knieverletzungen und bei 29 Spielern Fußgelenksverletzungen (35 Fußgelenke) vor. Die durchschnittliche Zeitspanne zwischen Verltzung und Untersuchung betrug 25 Jahre. Bei den Knieverletzungen gab es in 24 Fällen Risse des medialen kollateralen Bandes (MCL), in Kombination mit dem Riß des vorderen Kreuzbandes (ACL) und Meniskusläsionen in drei Fällen. Meniskusläsionen gab es in 17 Fällen, dabei drei in Kombination mit ACL und MCL und weiter zwei mit ACL-Rissen. Isolierte ACL-Risse gab es in vier Fällen. Bei den Fußgelenkvereltzungen gab es in 26 von 35 Fällen Risse des Seitenbandes. Insgesamt hatten 12 Spieler mit dem Fußball aufgehört und drei hatten den Beruf gewechselt. In 63% der Spieler mit Knie- und bei 33% der Spieler mit Fußgelenksverletzungen gab es Anzeichen von Arthritis. Die Häufigkeit von Arthritis in der Gruppe von 17 nicht verletzten Spielern lag bei 26% im Knie und 18% im Fußgelenk.